Metabolic Syndrome Is Associated With Altered mRNA and miRNA Content in Human Circulating Extracellular Vesicles - Li, Yongxin; Meng, Yu; Zhu, Xiangyang; Van Wijnen, Andre; Eirin, Alfonso; Lerman, Lilach O. (Frontiers in Endocrinology, 2021)
As mediators of intercellular communication, circulating extracellular vehicles (EVs) can modulate tissue and cellular pathways by altering transcription profiles in recipient cells, and their content may reflect the status of their parent cells. However, whether the metabolic syndrome (Mets) alters their cargo remains unclear. We hypothesized that MetS alters mRNA and miRNAs content packed within circulating-EVs. EVs were collected from plasma of patients with MetS or age-matched Lean controls (n=4 each). RNA-sequencing was performed to identify dysregulated mRNAs and miRNAs, and analyze genes targeted by miRNAs, top pathways, and diseases associated with MetS-EVs. MetS patients showed elevated body weight, blood pressure, glucose, insulin and liver injury markers levels. 1446 mRNAs were downregulated and 32 upregulated in MetS- compared to Lean-EVs, while 40 miRNAs were selectively enriched and 10 downregulated in MetS-EVs. MetS upregulated in EVs genes involved in apoptosis, mitochondrial regulation, transport, and lipoproteins, but downregulated vessel and heart development, protein complex biogenesis, and angiogenesis. MetS also upregulated miRNAs targeting genes implicated in cellular processes, including oxidation-reduction, and downregulated miRNAs capable of modulating catalytic activity, as well as heart, blood vessel, and skeletal development, transcriptional regulation, apoptosis, and cell cycle. Data from this study indicated that MetS modifies in human subjects the cargo of circulating EVs, which in turn may modulate several critical cellular functions and fate. These EV may reflect the anomalous status of their parent cells, and potentially serve as important regulators, biomarkers, and targets in the progression and treatment of MetS.